Diversity in Fish Auditory Systems: One of the Riddles of Sensory Biology - Ladich, Friedrich; Schulz-Mirbach, Tanja (Frontiers in Ecology and Evolution, 2016)
An astonishing diversity of inner ears and accessory hearing structures (AHS) that can enhance hearing has evolved in fishes. Inner ears mainly differ in the size of the otolith end organs, the shape and orientation of the sensory epithelia, and the orientation patterns of ciliary bundles of sensory hair cells. Despite our profound morphological knowledge of inner ear variation, two main questions remain widely unanswered. (i) What selective forces and/or constraints led to the evolution of this inner ear diversity? (ii) How is the morphological variability linked to hearing abilities? Improved hearing is mainly based on the ability of many fish species to transmit oscillations of swim bladder walls or other gas-filled bladders to the inner ears. Swim bladders may be linked to the inner ears via a chain of ossicles (in otophysans), anterior extensions (e.g. some cichlids, squirrelfishes), or the gas bladders may touch the inner ears directly (labyrinth fishes). Studies on catfishes and cichlids demonstrate that larger swim bladders and more pronounced linkages to the inner ears positively affect both auditory sensitivities and the detectable frequency range, but lack of a connection does not exclude hearing enhancement. This diversity of auditory structures and hearing abilities is one of the main riddles in fish bioacoustics research. Hearing enhancement might have evolved to facilitate intraspecific acoustic communication. A comparison of sound-producing species, however, indicates that acoustic communication is widespread in taxa lacking AHS. Eco-acoustical constraints are a more likely explanation for the diversity in fish hearing sensitivities. Low ambient noise levels may have facilitated the evolution of AHS, enabling fish to detect low-level abiotic noise and sounds from con- and heterospecifics, including predators and prey. Aquatic habitats differ in ambient noise regimes, and preliminary data indicate that hearing sensitivities of fishes vary accordingly.